Composition for lithium battery electrodes

JP2024515183A5Inactive Publication Date: 2025-03-19SOLVAY SPECIALTY POLYMERS ITALY SPA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023563952
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-04-19
Filing Date
2022-04-11
Publication Date
2025-03-19
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Increasing the molecular weight of fluoropolymers used as binders for lithium-ion battery electrodes enhances adhesion but increases the viscosity of electrode-forming formulations, making handling and coating processes more difficult.

Method used

A fluoropolymer composition containing randomly distributed hydroxyl and carboxyl group-containing vinyl monomers, with specific proportions and terminal groups, maintains low viscosity at low shear rates while ensuring high adhesion to current collectors.

Benefits of technology

The solution provides electrodes with excellent adhesion properties and manageable processing characteristics, facilitating easier manufacturing and improving the performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2022223347000001
    Figure 2022223347000001
  • Figure 2022223347000002
    Figure 2022223347000002
  • Figure 2022223347000003
    Figure 2022223347000003
Patent Text Reader

Abstract

The present invention relates to vinylidene fluoride copolymers comprising repeat units derived from hydrophilic monomers and to their use as binders for electrodes in Li-ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to European Patent Application No. 21169090.4, filed April 19, 2021, the entire contents of which are incorporated herein by reference for all purposes.

[0002] The present invention relates to vinylidene fluoride copolymers comprising repeat units derived from hydrophilic monomers and to their use as binders for electrodes in Li-ion batteries. [Background technology]

[0003] Fluoropolymers are known in the art to be suitable as binders for the manufacture of electrodes for use in electrochemical devices such as secondary batteries.

[0004] In particular, WO 2008 / 129041 (SOLVAY SPECIALTY POLYMERS ITALY SPA) discloses linear, semi-crystalline vinylidene fluoride (VDF) copolymers containing 0.05% to 10 mol % of repeat units derived from (meth)acrylic monomers, and their use as binders in electrodes for lithium-ion batteries.

[0005] In general, an increase in fluoropolymer molecular weight is known to improve the performance of articles made from these materials, especially in terms of mechanical properties and in terms of adhesion of the electrode to the current collector.

[0006] However, increasing the fluoropolymer molecular weight increases the viscosity of the electrode-forming formulation containing it, also called the electrode slurry, making the handling and coating process in the manufacture of the electrode much more difficult.

[0007] In the technical field of batteries, and in particular lithium batteries, the problem is felt of providing electrode binders characterized by very good adhesion without at the same time having adverse effects on the manufacturing process of the electrodes, such as by an increase in the viscosity of the slurry for their production.

[0008] The present invention provides a solution to this problem by combining the ease in the electrode manufacturing process by working with an electrode forming formulation that has low viscosity at low shear rates with the provision of an electrode that has very high adhesion to the current collector. Summary of the Invention

[0009] It has been discovered that certain vinylidene fluoride backbones, randomly containing certain hydroxyl- and carboxyl-containing vinyl monomers, and having certain chain end elements, are endowed with very good adhesion to metal substrates and can be used to prepare electrode-forming compositions having low viscosity at low shear rates.

[0010] Therefore, the object of the present invention is to - (i) repeat units derived from vinylidene fluoride (VDF) monomers; - (ii) repeat units derived from at least one hydroxyl-containing vinyl monomer (HA); - (iii) repeat units derived from at least one carboxyl group-containing vinyl monomer (CA), where the monomer (CA) is different from the monomer (HA); A fluoropolymer [polymer (F)] comprising the total amount of monomers (HA) and (CA) in said polymer (F) is at least 0.01 mol %, more preferably at least 0.02 mol %, more preferably at least 0.02 mol % and at most 5.0 mol %, preferably at most 1.5 mol %, relative to the total moles of repeating units of polymer (F); a proportion of at least 40% of the monomers (HA) and at least 40% of the monomers (CA) are randomly distributed in said polymer (F); The polymer (F) has the formula (I): -(R a ) x -RO-R b (I) (wherein RO is a divalent group containing at least one oxygen atom; R a is a C1 to C5 linear or branched hydrocarbon group, R b is hydrogen or a C1-C5 linear or branched hydrocarbon group, and x is an integer selected from 1 and zero. and the end groups are present in an amount of at least 1 / 10000 VDF unit, preferably more than 1.5 / 10000 VDF unit, more preferably more than 2 / 10000 VDF unit; The polymer (F) is the object of the present invention.

[0011] The second object of the present invention is to a) at least one electrode active material (AM); b) at least one binder (B), where the binder (B) comprises at least one polymer (F) as defined above; c) at least one solvent (S); The present invention relates to an electrode-forming composition (C) comprising the above compound.

[0012] In another aspect, the present invention relates to the use of the electrode-forming composition (C) in a process for the manufacture of an electrode [electrode (E)], said process comprising: (A) providing a metal substrate having at least one surface; (B) providing an electrode-forming composition [composition (C)] as defined above; (C) applying the composition (C) provided in step (B) onto at least one surface of the metal substrate provided in step (A), thereby providing an assembly comprising a metal substrate coated on at least one surface with said composition (C); (D) drying the assembly provided in step (C); (E) subjecting the dried assembly obtained in step (D) to a compression step to obtain the electrode (E) of the present invention. Including, regarding use.

[0013] In a further object, the present invention relates to an electrode [electrode (E)] obtainable by the process of the invention.

[0014] In a still further object, the present invention relates to an electrochemical device comprising at least one electrode (E) of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The term "repeating unit derived from vinylidene fluoride" (also commonly designated vinylidene difluoride, 1,1-difluoroethylene, VDF) is intended to mean a repeating unit of the formula CF2=CH2.

[0016] Suitable hydroxyl group-containing vinyl monomers (HA) are represented by formula (I): [ka] (In the formula: R1, R2 and R3, which are equal to or different from each other, are independently selected from a hydrogen atom, a halogen atom, and a C1-C3 hydrocarbon group; R OH is a C2-C alkyl group containing at least one hydroxyl group and optionally containing one or more oxygen atoms, carbonyl groups or carboxy groups in the chain. 10 (the hydrocarbon chain portion) It is a compound of the formula:

[0017] In a preferred embodiment, the monomer (HA) has the formula (Ia): [ka] (In the formula: R1, R2 and R3, which are equal to or different from each other, are independently selected from a hydrogen atom and a C1-C3 hydrocarbon group; R' OHis a C1-C5 hydrocarbon moiety containing at least one hydroxyl group. It is a compound of the formula:

[0018] Non-limiting examples of monomers (HA) of formula (Ia) include, inter alia: - Hydroxyethyl (meth)acrylate (HEA), - 2-hydroxypropyl acrylate (HPA), - hydroxyethylhexyl (meth)acrylate, and mixtures thereof Includes:

[0019] Preferably, the at least one monomer (HA) is hydroxyethyl (meth)acrylate (HEA) or 2-hydroxypropyl acrylate (HPA).

[0020] Suitable carboxyl group-containing vinyl monomers (CA) are represented by the formula (II): [ka] (In the formula: R1, R2 and R3, which are equal to or different from each other, are independently selected from a hydrogen atom and a C1-C3 hydrocarbon group; R H contains at least one carboxyl group and no hydroxyl group, C2-C 10 (the hydrocarbon portion) It is a compound of the formula:

[0021] In a preferred embodiment, the monomer (CA) has the formula (IIa): [ka] (In the formula, R1, R2 and R3, which are equal to or different from each other, are independently selected from a hydrogen atom and a C1-C3 hydrocarbon group; R' H is hydrogen or a C1-C5 hydrocarbon moiety containing at least one carboxyl group and no hydroxyl groups. It is a compound of the formula:

[0022] R' H may further contain one or more oxygen atoms, carbonyl groups or ester groups in the chain.

[0023] Non-limiting examples of monomers (CA) of formula (IIa) include, inter alia: - Acrylic acid (AA) and (Meth)acrylic acid, - 2-carboxyethyl (meth)acrylate, - (meth)acryloyloxyethyl succinate, - (meth)acryloyloxypropyl succinic acid, and mixtures thereof Includes:

[0024] Preferably, at least one monomer (CA) is acrylic acid (AA).

[0025] The molar ratio between repeating units (ii) and (iii) in polymer (F) is preferably comprised within the range of 20:1 to 1:20, preferably 10:1 to 1:10, more preferably 1:5 to 5:1.

[0026] It is essential that in polymer (F) at least a 40% proportion of monomers (HA) and at least a 40% proportion of monomers (CA) are randomly distributed in said polymer (F).

[0027] The expression "proportion of randomly distributed monomers (HA)" is defined by the following formula:

number

[0028] If each (HA) repeat unit is isolated, i.e. contained between two repeat units of a VDF monomer, the average number of (HA) sequences is equal to the average total number of (HA) repeat units and therefore the proportion of randomly distributed units (HA) is 100%: this value corresponds to a completely random distribution of the (HA) repeat units.

[0029] Thus, as stated above, the greater the number of isolated (HA) units relative to the total number of (HA) units, the higher the percentage value of the proportion of randomly distributed units (HA) will be.

[0030] The expression "proportion of randomly distributed monomers (CA)" is defined by the following formula:

number

[0031] If each of the (CA) repeat units is isolated, i.e. contained between two repeat units of a VDF monomer, the average number of (CA) sequences is equal to the average total number of (CA) repeat units, and therefore the proportion of randomly distributed units (HA) is 100%: this value corresponds to a completely random distribution of the (CA) repeat units. Thus, as stated above, the greater the number of isolated (CA) units relative to the total number of (CA) units, the higher the percentage value of the proportion of randomly distributed units (CA) will be.

[0032] Determination of the total average number of (HA) and (CA) monomer repeat units in polymer (F) can be carried out by any suitable method, with NMR being preferred.

[0033] The proportion of randomly distributed units (HA) and (CA) is preferably at least 50%, more preferably at least 60%, most preferably at least 70%.

[0034] The polymer (F) preferably contains at least 0.01%, more preferably at least 0.02 mol % of repeat units derived from said monomer (HA).

[0035] Polymer (F) preferably comprises at most 5.0%, more preferably at most 3.0 mol %, even more preferably at most 2.0 mol % of repeat units derived from monomer (HA).

[0036] The polymer (F) preferably contains at least 0.01%, more preferably at least 0.02 mol % of repeat units derived from said monomer (CA).

[0037] Polymer (F) preferably comprises at most 5.0%, more preferably at most 3.0 mol %, even more preferably at most 2.0 mol % of repeat units derived from monomer (CA).

[0038] Excellent results have been obtained with polymers (F) which contain at least 70 mol % of repeat units derived from VDF.

[0039] The polymer (F) can be an elastomeric or semi-crystalline polymer, preferably a semi-crystalline polymer.

[0040] As used herein, the term "semi-crystalline" refers to a fluoropolymer that has at least one crystalline melting point in addition to the glass transition temperature Tg in DSC analysis. For the purposes of the present invention, semi-crystalline fluoropolymer is intended herein to mean a fluoropolymer that has a heat of fusion of 10-90 J / g, preferably 30-80 J / g, more preferably 35-75 J / g, as measured according to ASTM D3418-08.

[0041] For the purposes of the present invention, the term "elastomer" is intended to denote a true elastomer or a polymer resin that serves as a building block to obtain a true elastomer.

[0042] True elastomers are defined by ASTM, Special Technical Bulletin, Standard No. 184, as materials which, at room temperature, can be stretched to twice their inherent length and which, when held under tension for 5 minutes and then released, simultaneously return to within 10% of their original length.

[0043] Preferably, the intrinsic viscosity of the polymer (F), measured in dimethylformamide at 25° C., is from 0.05 l / g to 0.70 l / g, more preferably from 0.20 l / g to 0.50 l / g.

[0044] The polymer (F) of the present invention usually has a melting temperature (Tm) within the range of 130 to 200°C.

[0045] The polymer (F) of the invention has a quasi-linear structure with very little branching, resulting in an insoluble fraction due to a substantial reduction in long branched chains.

[0046] The polymer (F) of the present invention in fact preferably has a low proportion of insoluble components in standard polar aprotic solvents for PVDF, such as NMP, and more preferably, solutions of the polymer (F) in said standard polar aprotic solvents remain homogeneous and stable for several weeks, substantially without insoluble residues.

[0047] Due to the small amount of insoluble components, the GPC and NMR analysis of the polymer (F) is not affected and there are no reliability and reproducibility problems.

[0048] The melting temperature can be determined from a DSC curve obtained by differential scanning calorimetry (hereinafter also referred to as DSC). When the DSC curve shows multiple melting peaks (endothermic peaks), the melting temperature (Tm) is determined based on the peak with the largest peak area.

[0049] The polymer (F) may further comprise repeat units derived from one or more fluorinated comonomers (CF) different from VDF.

[0050] The term "fluorinated comonomer (CF)" is intended herein to mean an ethylenically unsaturated comonomer that contains at least one fluorine atom.

[0051] Non-limiting examples of suitable fluorinated comonomers (CF) include, inter alia: (a) C2-C8 fluoro and / or perfluoroolefins such as tetrafluoroethylene (TFE), hexafluoropropylene (HFP), pentafluoropropylene and hexafluoroisobutylene; (b) C2 to C8 hydrogen-containing monofluoroolefins such as vinyl fluoride, 1,2-difluoroethylene, and trifluoroethylene; (c)Formula CH2=CH-R f0 (In the formula, R f0 is a C1-C6 perfluoroalkyl group; (d) Chloro-, and / or bromo-, and / or iodo-C2-C6 fluoroolefins such as chlorotrifluoroethylene (CTFE). Includes:

[0052] The fluorinated comonomer (CF) is preferably HFP.

[0053] In one preferred embodiment, the polymer (F) is semi-crystalline and contains 0.1 to 15.0 mol %, preferably 0.3 to 5.0 mol %, more preferably 0.5 to 3.0 mol % of repeat units derived from said fluorinated comonomer (CF).

[0054] It is understood that moieties of chain ends, defects or other impurity types different from those defined above can be contained in the polymer (F) without these impairing its properties.

[0055] The polymer (F) is more preferably at least 80 mol %, preferably at least 85 mol %, of vinylidene fluoride (VDF); - 0.01 mol % to 1.5 mol %, preferably 0.05 mol % to 1.0 mol %, of at least one hydroxyl group-containing vinyl monomer (HA); - 0.01 mol % to 1.5 mol %, preferably 0.05 mol % to 1.0 mol %, of at least one carboxyl group-containing vinyl monomer (CA); - optionally, 0.5 to 3.0 mol % of repeat units derived from at least one fluorinated comonomer (CF) It contains repeating units derived from:

[0056] The polymer (F) of the present invention has the formula (I): -(R a ) x -RO-R b (I) (In the formula: RO is a divalent radical containing at least one oxygen atom, - R a is a C1 to C5 linear or branched hydrocarbon group, - R b is hydrogen or a C1 to C5 linear or branched hydrocarbon group, - x is an integer selected from 1 and zero. and Said end groups are present in an amount of at least 1 / 10000 VDF unit, preferably more than 2 / 10000 VDF unit.

[0057] Non-limiting examples of divalent groups RO include, inter alia: Ether (-O-), Esters (-O-CO-), Ketones (-CO-), Epoxides, and Percarbonate (-O-CO-O-) group Includes:

[0058] In a preferred embodiment of the present invention, RO is a divalent group containing at least two oxygen atoms. More preferably, RO is a percarbonate group.

[0059] Preferably, R a and R b are both C2 to C3 linear or branched hydrocarbon groups, more preferably C3 linear or branched hydrocarbon groups.

[0060] Preferably, x is zero.

[0061] The polymer (F) of the invention may be obtained by polymerization of VDF monomer, at least one monomer (HA), at least one monomer (CA) and optionally at least one comonomer (CF), either in suspension in an organic medium, for example according to the procedures described in WO2008129041, or in aqueous emulsion, typically carried out as described in the art (see for example US Pat. Nos. 4,016,345, 4,725,644 and 6,479,591).

[0062] A preferred procedure for preparing the polymer (F) comprises the polymerization of vinylidene fluoride (VDF) monomer, monomer (HA) and monomer (CA), and optionally comonomer (CF), in an aqueous medium in the presence of a radical initiator, said process comprising: - continuously supplying an aqueous solution comprising monomer (HA) and monomer (CA); - maintaining the pressure in said reactor above the critical pressure of vinylidene fluoride; Includes.

[0063] Suitable initiators known for the polymerization of fluorinated monomers are organic peroxides, such as those selected from the group consisting of dialkyl peroxides, diacyl-peroxides, peroxyesters, and peroxydicarbonates.

[0064] Exemplary dialkyl peroxides are di-t-butyl peroxide, and among the peroxyesters are t-butyl peroxypivalate and t-amyl peroxypivalate, and among the peroxydicarbonates are di(ethyl) peroxydicarbonate, di(n-propyl) peroxydicarbonate, diisopropyl peroxydicarbonate, di(sec-butyl) peroxydicarbonate, di(2-ethylhexyl) peroxydicarbonate, and di(4-tert-butylcyclohexyl) peroxydicarbonate.

[0065] Preferably, the initiator used to prepare the polymer (F) of the present invention is an organic peroxide, more preferably selected from di(ethyl)peroxydicarbonate, di(n-propyl)peroxydicarbonate, di(iso-propyl)peroxydicarbonate and di(4-tert-butylcyclohexyl)peroxydicarbonate.

[0066] The amount of initiator required for polymerization depends on its activity and the temperature used for polymerization. The total amount of initiator used is generally 100-30000 ppm by weight based on the total monomer weight used.

[0067] The initiator may be added in pure form, in a solution, in a suspension, or in an emulsion, depending on the initiator selected.

[0068] A chain transfer agent, CTA, can be added to the polymerization. Suitable CTAs for this polymerization are known in the art and are typically short hydrocarbon chains such as ethane and propane, esters such as ethyl acetate or diethyl maleate, diethyl carbonate, etc. If an organic peroxide is used as an initiator, it could also serve as an effective CTA during the progress of the free radical polymerization. However, additional CTA can be added all at once at the beginning of the reaction, or it can be added in portions or continuously throughout the progress of the reaction. The amount of CTA and its mode of addition depend on the desired properties.

[0069] In a preferred preparation process, the pressure is maintained above the critical pressure of vinylidene fluoride. Generally, the pressure is maintained at a value above 50 bar, preferably above 75 bar, and even more preferably above 100 bar.

[0070] It is essential that a continuous supply of the aqueous solution containing monomer (HA) and monomer (CA) is carried out, usually for the entire duration of the polymerization run.

[0071] It is therefore possible to obtain an approximately statistical distribution of both monomers (HA) and monomers (CA) within the VDF monomer polymer backbone of polymer (F).

[0072] The expressions "continuous feed" or "continuous feed" mean that slow, small, incremental additions of the aqueous solution of monomer (HA) and monomer (CA) are made until the polymerization is complete.

[0073] The aqueous solution of monomer (HA) and monomer (CA) is continuously fed during polymerization for an amount of at least 50% by weight of the total amount of monomer (HA) and monomer (CA) fed during the reaction (i.e. initial charge plus continuous feed). Preferably, at least 60% by weight, more preferably at least 70% by weight, most preferably at least 80% by weight of the total amount of monomer (HA) and monomer (CA) is continuously fed during polymerization. Even if this requirement is not essential, gradually increasing addition of VDF monomer can be achieved during polymerization. Generally, the process of the present invention is carried out at a temperature of at least 35°C, preferably at least 40°C, more preferably at least 45°C.

[0074] When the polymerization is carried out in suspension, the polymer (F) is typically provided in the form of a powder.

[0075] When the polymerization to obtain the polymer (F) is carried out in emulsion, the polymer (F) typically comes in the form of an aqueous dispersion (D), which can be used as obtained directly by emulsion polymerization or after a concentration step.

[0076] The polymer (F) obtained by emulsion polymerization can be isolated from the aqueous dispersion (D) by concentration and / or coagulation of the dispersion and obtained in powder form by subsequent drying.

[0077] The polymer (F) in the form of a powder can optionally be further extruded to obtain the polymer (F) in the form of pellets.

[0078] The polymer (F) as detailed above may be used as a binder for electrodes of Li-ion batteries.

[0079] The second object of the present invention is to a) at least one electrode active material (AM); b) at least one binder (B), where the binder (B) comprises at least one polymer (F) as defined above; c) at least one solvent (S); d) optionally, at least one conductive agent; The present invention relates to an electrode-forming composition (C) comprising the above compound.

[0080] For the purposes of the present invention, the term "electroactive material (AM)" is intended to mean a compound capable of incorporating or intercalating into its structure and subsequently releasing therefrom alkali or alkaline earth metal ions during the charging and discharging phases of an electrochemical device. The compound (AM) is preferably capable of incorporating or intercalating and releasing lithium ions.

[0081] The nature of compound (AM) in composition (C) depends on whether said composition is used for the manufacture of a positive electrode [electrode (Ep)] or a negative electrode [electrode (En)].

[0082] When forming a positive electrode (Ep) for a lithium-ion secondary battery, the compound (AM) may include a complex metal chalcogenide of the formula LiMQ2, where M is at least one metal selected from transition metals such as Co, Ni, Fe, Mn, Cr and V, or metals such as Al, and mixtures thereof, and Q is a chalcogen such as O or S. Among these, it is preferable to use a lithium-based complex metal oxide of the formula LiMO2, where M is the same as defined above. Preferred examples thereof include LiCoO2, LiNiO2, LiNi x Co 1-x O2(0 <x<1)、LiNi a Co b Al c Alternatively, when forming a positive electrode (Ep) for a lithium ion secondary battery, the compound (AM) may be of the formula M1M2(JO4): f E 1-fwhere M1 is lithium, which may be partially replaced with another alkali metal representing less than 20% of the M1 metal; M2 is a transition metal at an oxidation level of +2 selected from Fe, Mn, Ni or mixtures thereof, which may be partially replaced with one or more additional metals at an oxidation level between +1 and +5, including 0, representing less than 35% of the M2 metal; JO4 is any oxyanion, where J is any of P, S, V, Si, Nb, Mo or combinations thereof; E is a fluoride, hydroxide or chloride anion; and f is the mole fraction of the JO4 oxyanion, generally comprised between 0.75 and 1.

[0083] M1M2(JO4) as defined above f E 1-f The electroactive material is preferably phosphate-based and may have an ordered or modified olivine structure.

[0084] More preferably, the compound (AM) when forming the positive electrode (Ep) has the formula Li 3-x M' y M'' 2-y (JO4)3, where 0≦x≦3, 0≦y≦2, M′ and M″ are the same or different metals, at least one of which is a transition metal, and JO4 is preferably PO4, which may be partially substituted with another oxyanion, where J is any of S, V, Si, Nb, Mo or combinations thereof. Even more preferably, the compound (AM) has the formula Li(Fe x Mn 1-x )PO4, where 0≦x≦1, and x is preferably 1 (i.e., lithium iron phosphate of formula LiFePO4).

[0085] In the case of forming a composite negative electrode (En) for a lithium-ion secondary battery, the compound (AM) may preferably comprise a carbon-based material and / or a silicon-based material.

[0086] In some embodiments, the carbon-based material can be graphite, graphene, or carbon black, such as, for example, natural or artificial graphite.

[0087] These materials may be used alone or as a mixture of two or more of them.

[0088] The carbon-based material is preferably graphite.

[0089] The silicon-based compound may be one or more selected from the group consisting of chlorosilane, alkoxysilane, aminosilane, fluoroalkylsilane, silicon, silicon chloride, silicon carbide, and silicon oxide. More specifically, the silicon-based compound may be silicon oxide or silicon carbide.

[0090] When present in compound (AM), the at least one silicon-based compound is contained in compound (AM) in an amount ranging from 1 to 30% by weight, preferably from 5 to 20% by weight, based on the total weight of compound (AM).

[0091] The solvent (S) may be preferably an organic polar solvent, examples of which may include: N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethylsulfoxide, hexamethylphosphamide, dioxane, tetrahydrofuran, tetramethylurea, triethylphosphate, and trimethylphosphate. These solvents may be used alone or in mixtures of two or more species.

[0092] An optional conductive agent may be added to improve the conductivity of the resulting electrode (AM).

[0093] Examples of these may include: carbon black, graphite fine powder, carbonaceous materials such as carbon nanotubes (CNT), graphene, or fibers, or fine powders or fibers of metals such as nickel or aluminum. The optional conductive agent is preferably carbon black. Carbon black is available, for example, under the brand names Super P® or Ketjenblack®.

[0094] When present, the conductive agent is different from the carbon-based material described above.

[0095] In a preferred embodiment of the present invention, an electrode-forming composition (C) for use in preparing a positive electrode (Ep) is provided, said composition comprising: a) at least one electrode active material (AM); b) at least one binder (B), where the binder (B) comprises at least one polymer (F) as defined above; c) at least one solvent (S); d) at least one conductive agent, preferably selected from carbon black or graphite fine powder and carbon nanotubes; Includes.

[0096] As mentioned above, the polymer (F) of the present invention has a quasi-linear structure and a very small insoluble fraction when dissolved in standard polar aprotic solvents such as NMP.

[0097] Due to the small amount of insoluble components, polymer (F) provides a solution in organic solvents that is not adversely affected by the presence of insoluble residues, commonly referred to as "gels," and is therefore more suitable for use in formulating electrode-forming compositions.

[0098] In another object, the present invention relates to the use of the electrode-forming composition (C) for the manufacture of an electrode [electrode (E)], said process comprising: (A) providing a metal substrate having at least one surface; (B) providing an electrode-forming composition [composition (C)] as defined above; (C) applying the composition (C) provided in step (B) onto at least one surface of the metal substrate provided in step (A), thereby providing an assembly comprising a metal substrate coated on at least one surface with said composition (C); (D) drying the assembly provided in step (C); (E) subjecting the dried assembly obtained in step (iv) to a compression step to obtain the electrode (E) of the present invention. Includes.

[0099] In a further object, the present invention relates to an electrode [electrode (E)] obtainable by the process of the present invention.

[0100] The applicant has surprisingly found that the electrode (E) of the present invention exhibits outstanding adhesion of the binder to the current collector.

[0101] The electrode (E) of the invention is therefore particularly suitable for use in electrochemical devices, in particular in secondary batteries.

[0102] For the purposes of the present invention, the term "secondary battery" is intended to mean a rechargeable battery.

[0103] The secondary battery of the present invention is preferably an alkali metal secondary battery or an alkaline earth metal secondary battery.

[0104] The secondary battery of the present invention is more preferably a lithium ion secondary battery.

[0105] In a still further object, the present invention relates to an electrochemical device comprising at least one electrode (E) of the present invention.

[0106] The electrochemical device according to the present invention, which is preferably a secondary battery, comprises: - Positive and negative electrodes Including, Here, at least one of the positive electrode and the negative electrode is the electrode (E) of the present invention.

[0107] In one preferred embodiment of the present invention, - Positive and negative electrodes Including, Here, an electrochemical device is provided which is a secondary battery in which the negative electrode is the electrode (E) according to the present invention.

[0108] Electrochemical devices according to the present invention can be prepared by standard methods known to those skilled in the art.

[0109] To the extent that the disclosures of any patents, patent applications, and publications incorporated herein by reference conflict with the statements of this application to the extent that a term may be unclear, this statement shall control.

[0110] The present invention will now be described with reference to the following examples, the purposes of which are merely illustrative and are not intended to limit the scope of the invention. EXAMPLES

[0111] Determination of the intrinsic viscosity of the polymer (F) The intrinsic viscosity (η) [dl / g] was calculated based on the dropwise addition time of a solution obtained by dissolving the polymer (F) in N,N-dimethylformamide at a concentration of about 0.2 g / dl using an Ubbelhode viscometer at 25° C., according to the following equation:

number

[0112] DSC analysis DSC analysis was performed according to the ASTM D 3418 standard, and the melting point (T f2 ) was determined at a heating rate of 10 °C / min.

[0113] Determination of polar end groups The amount of polar end groups resulting from the initiator diethyl peroxydicarbonate used in the polymerization process is measured by measuring the intensity of the H atom of the CH2 group (in bold in the formula below) relative to the total intensity of the CH2 moieties of the polymer (F) backbone VDF monomer units. 1 Determined by H-NMR. [ka]

[0114] The content of the terminal group is determined by the following formula: [EG]=(I EG / I VDF ) x 10000 (In the formula: - [EG] is the overall end group content expressed as moles per 10000 VDF units; -I EG is the intensity of the integral of the end group [EG], normalized to one hydrogen; -I VDF is the intensity, normalized to one hydrogen, of the integrals of the normal and inverted VDF repeat units) was calculated by applying

[0115] Approximately 20 mg of polymer was dissolved in 0.7 ml of hexadeuteroacetone. 1 The 1 H-NMR spectrum showed the aforementioned CH2 at 4.24 ppm, while the CH2 signals from the VDF normal and reverse repeat units resonated as broad peaks centered at 3.2 and 2.5 ppm, respectively.

[0116] Example 1: Preparation of Polymer F-1 Into a 4 L reactor equipped with an impeller rotating at a speed of 650 rpm: 2,014 g of demineralized water and a solution of 0.4 g of PEO (Alkox®-E45 from Alkorox) per kg of total VDF monomers and 0.5 g of hydroxypropylmethylcellulose (Methocel®-K100 from Dow) per kg of total VDF monomers and 59.91 g of trisodium phosphate were successively introduced. The oxygen present in the reactor was removed by a sequence of vacuum and nitrogen purge at a fixed temperature of 14° C. This sequence was repeated three times.

[0117] Then 30 g of demineralized water, 11.28 g of hydrogen peroxide (Brenntag) and 3.53 g of ethyl chloroformate (Framochem) were introduced into the reactor.

[0118] After 15 minutes, 0.28 g of acrylic acid (AA) and 0.07 g of hydroxyethyl acrylate (HEA) were introduced into the reactor at a stirring speed of 880 rpm. Shortly after, 1.166 g of VDF was added to the mixture. The reactor was then gradually heated until a set point temperature of 45° C. was reached, corresponding to a reactor pressure of 120 bar.

[0119] The pressure was kept constant at 120 bar throughout the entire polymerization run by feeding an aqueous solution containing 9.40 g AA per liter of solution and 4.70 g HEA per liter of solution. After 365 minutes, the polymerization was stopped by degassing the suspension until atmospheric pressure was reached. A total of 721 g of AA and HEA solution was charged to the reactor.

[0120] The polymer was then collected by filtration and suspended in clean water in a stirred tank. After washing, the polymer was dried in an oven at 65° C. for 12 hours. 919 g of dry powder was recovered.

[0121] Intrinsic viscosity of 0.28 l / g in DMF at 25°C and T 2f A polymer containing VDF-AA (0.45 mol %)-HEA (0.15 mol %) having the formula:

[0122] The polymer contained the end group CH3CH2-OCOO- at 3.0 / 10000 VDF units.

[0123] In addition, the presence of -CF2H at 4.5 / 10000 VDF units and -CF2CH3 at 2.5 / 10000 VDF units was determined.

[0124] Example 2: Preparation of Polymer F-2 Into a 4 L reactor equipped with an impeller rotating at a speed of 650 rpm: 1,983 g of demineralized water and 0.4 g of PEO (Alkox®-E45 from Alkorox) per kg of total VDF monomers and 0.5 g of hydroxypropylmethylcellulose (Methocel®-K100 from Dow) per kg of total VDF monomers and 87.89 g of trisodium phosphate were successively introduced. The oxygen present in the reactor was removed by a sequence of vacuum and nitrogen purge at a fixed temperature of 14° C. This sequence was repeated three times.

[0125] Then 100 g of demineralized water, 15.66 g of hydrogen peroxide (Brenntag) and 5 g of ethyl chloroformate (Framochem) were introduced into the reactor.

[0126] After 15 minutes, 0.39 g of acrylic acid (AA) and 0.047 g of hydroxypropyl acrylate (HPA) were introduced into the reactor at a stirring speed of 880 rpm. Shortly after, 1.165 g of VDF was added to this mixture. The reactor was then gradually heated until a set point temperature of 40° C. was reached, corresponding to a reactor pressure of 120 bar.

[0127] The pressure was kept constant at 120 bar throughout the entire polymerization run by feeding an aqueous solution containing 13.75 g AA per liter of solution and 1.66 g HPA per liter of solution. After 429 minutes, the polymerization was stopped by degassing the suspension until atmospheric pressure was reached. A total of 681 g of AA and HPA solution was charged to the reactor.

[0128] The polymer was then collected by filtration and suspended in clean water in a stirred tank. After washing, the polymer was dried in an oven at 65° C. for 12 hours. 872 g of dry powder was recovered.

[0129] Intrinsic viscosity of 0.249 l / g in DMF at 25°C and T 2f The polymer VDF-AA (0.7 mol %)-HPA (0.05 mol %) having the formula

[0130] This polymer contained the end group CH3CH2-OCOO- at 2.8 / 10000 VDF units.

[0131] In addition, the presence of -CF2H at 4.8 / 10000 VDF units and -CF2CH3 at 2.1 / 10000 VDF units was determined.

[0132] Example 3: Preparation of Polymer F-3 Into a 4 L reactor equipped with an impeller rotating at a speed of 650 rpm: 1,932 g of demineralized water and a solution of 0.4 g of PEO (Alkox®-E45 from Alkorox) per kg of total VDF monomers and 0.5 g of hydroxypropylmethylcellulose (Methocel®-K100 from Dow) per kg of total VDF monomers and 124.08 g of trisodium phosphate were successively introduced. The oxygen present in the reactor was removed by a sequence of vacuum and nitrogen purge at a fixed temperature of 14° C. This sequence was repeated three times.

[0133] Then 100 g of demineralized water, 22.11 g of hydrogen peroxide (Brenntag) and 7.06 g of ethyl chloroformate (Framochem) were introduced into the reactor.

[0134] After 15 minutes, 0.39 g of acrylic acid (AA) and 0.046 g of hydroxypropyl acrylate (HPA) were introduced into the reactor at a stirring speed of 880 rpm. Shortly after, 1.165 g of VDF was added to the mixture. The reactor was then gradually heated until a set point temperature of 40° C. was reached, corresponding to a reactor pressure of 120 bar.

[0135] The pressure was kept constant at 120 bar throughout the entire polymerization run by feeding an aqueous solution containing 13.38 g AA per liter of solution and 1.61 g HPA per liter of solution. After 369 minutes, the polymerization was stopped by degassing the suspension until atmospheric pressure was reached. A total of 700 g of AA and HPA solution was charged to the reactor.

[0136] The polymer was then collected by filtration and suspended in clean water in a stirred tank. After washing, the polymer was dried in an oven at 65° C. for 12 hours. 864 g of dry powder was recovered.

[0137] Intrinsic viscosity of 0.207 l / g in DMF at 25°C and a T 2f The polymer VDF-AA (0.7 mol %)-HPA (0.05 mol %) having the formula

[0138] This polymer contained the end group CH3CH2-OCOO- at 3.6 / 10000 VDF units.

[0139] In addition, the presence of -CF2H at 5.0 / 10000 VDF units and -CF2CH3 at 2.3 / 10000 units was determined.

[0140] Example 4 Comparison: Preparation of Polymer A Into a 4 L reactor equipped with an impeller rotating at a speed of 650 rpm: 1.928 g of demineralized water and 0.4 g of PEO (Alkox®-E45 from Alkorox) per kg of total VDF monomers and 0.5 g of hydroxypropylmethylcellulose (Methocel®-K100 from Dow) per kg of total VDF monomers were successively introduced. The oxygen present in the reactor was removed by a sequence of vacuum and nitrogen purge at a fixed temperature of 11° C. This sequence was repeated three times.

[0141] Then, 0.39 g of acrylic acid (AA) and 6.77 g of a solution (75%) of initiator t-amyl perpivalate (United Initiators) in isododecane were introduced into the reactor. Shortly after, 1,164 g of VDF were added to this mixture. The reactor was then gradually heated until a set point temperature of 50° C. was reached, corresponding to a reactor pressure of 120 bar.

[0142] The pressure was kept constant at 120 bar throughout the entire polymerization run by feeding an aqueous solution containing 11.91 g of AA per liter of solution and 1.49 g of hydroxypropyl acrylate (HPA) per liter of solution. After 480 minutes, the polymerization was stopped by degassing the suspension until atmospheric pressure was reached. A total of 787 g of AA and HPA solution was charged to the reactor.

[0143] The polymer was then collected by filtration and suspended in clean water in a stirred tank. After washing, the polymer was dried in an oven at 65° C. for 12 hours. 896 g of dry powder was recovered.

[0144] Polymer VDF-AA (0.7 mol%)-HPA (0.05 mol%), with an intrinsic viscosity of 0.231 l / g in DMF at 25° C. and a T 2f A polymer having the formula:

[0145] The polymer contained -C(CH3)3 at 2.2 / 10000 VDF units, -CF2H at 6.4 / 10000 VDF units and -CF2CH3 at 2.7 / 10000 VDF units.

[0146] The end group CH3CH2-OCOO- was absent.

[0147] General preparation of electrodes using NMC active material A positive electrode with a final composition of 96.5 wt % NMC, 1.5 wt % polymer, 2 wt % conductive additive was prepared as follows.

[0148] A first dispersion was prepared by premixing 34.7 g of a 6 wt % solution of polymer in NMP, 133.8 g of NMC, 2.8 g of SC-65, and 8.8 g of NMP in a centrifugal mixer for 10 minutes.

[0149] The mixture was then mixed with a high-speed disk impeller at 2000 rpm for 50 minutes. An additional 7.2 g of NMP was then added to the dispersion, which was further mixed with a butterfly impeller at 1000 rpm for 20 minutes. The resulting composition was cast onto an Al foil with a thickness of 15 μm using a doctor blade, and the coated layer was dried in a vacuum oven at a temperature of 90° C. for about 50 minutes to obtain a positive electrode. The thickness of the dried coating layer was about 110 μm.

[0150] Measurement of slurry viscosity Slurry viscosity was measured on an AntonPaar Rheolab QC using a concentric cylinder setup (Measuring Cup: C-CC27 / QC-LTD Bob: CC27 / P6) with peltier temperature control at 25° C. Steady state viscosity was measured from shear rates of 0.1 to 200 l / s.

[0151] Adhesion Measurement Adhesion peel strength between aluminum foil and electrode: To evaluate the adhesion of the dried coating layer to the Al foil, a 180° peel test was performed according to the set-up described in standard ASTM D903 at 20° C. and a speed of 300 mm / min.

[0152] Example 5: Adhesion and Slurry Viscosity Using the polymers of Examples 1 to 4 as binders, electrode compositions were prepared according to the procedures set forth above. The slurry viscosity and adhesion values ​​are shown in Table 1.

[0153] [Table 1]

[0154] The results show that the polymers of the present invention are more functional and easier to handle in the electrode manufacturing process due to their low slurry viscosity and good adhesion.

Claims

1. A fluoropolymer [polymer (F)] comprising: (i) repeat units derived from vinylidene fluoride (VDF) monomers; - (ii) repeat units derived from at least one hydroxyl group-containing vinyl monomer (HA); (iii) a repeating unit derived from at least one carboxyl group-containing vinyl monomer (CA) different from the monomer (HA); A fluoropolymer [polymer (F)] comprising: the total amount of monomers (HA) and (CA) in said polymer (F) is at least 0.01 mol %, more preferably at least 0.02 mol %, more preferably at least 0.02 mol % and at most 5.0 mol %, preferably at most 1.5 mol %, relative to the total moles of repeating units of polymer (F); a proportion of at least 40% of the monomers (HA) and at least 40% of the monomers (CA) being randomly distributed in said polymer (F); The polymer (F) has the formula (I): -(R a ) x -RO-R b (I) (wherein RO is a divalent group containing at least one oxygen atom; R a is C 1 ~C 5 R is a linear or branched hydrocarbon group. b is hydrogen or C 1 ~C 5 and x is an integer selected from 1 and zero. and said end groups being present in an amount of at least 1 / 10000 VDF unit, preferably more than 1.5 / 10000 VDF unit, more preferably more than 2 / 10000 VDF unit; Polymer (F).

2. The hydroxyl group-containing vinyl monomer (HA) has the formula (I): 【Chemistry 1】 (In the formula: R is equal to or different from 1 , R 2 and R 3 is a hydrogen atom, a halogen atom, and C 1 ~C 3 R is independently selected from a hydrocarbon group; OH is a C 2 -C 10 hydrocarbon chain moiety containing at least one hydroxyl group and optionally one or more oxygen atoms, carbonyl groups or carboxy groups in the chain; The polymer (F) according to claim 1, which is a compound represented by the formula:

3. The monomer (HA) has the formula (Ia): 【Chemistry 2】 (In the formula: R is equal to or different from 1 , R 2 and R 3 is a hydrogen atom and C 1 ~C 3 R' is independently selected from a hydrocarbon group; OH is a C acrylate containing at least one hydroxyl group, preferably selected from the group consisting of hydroxyethyl (meth)acrylate (HEA), 2-hydroxypropyl acrylate (HPA), hydroxyethylhexyl (meth)acrylate, and mixtures thereof; 1 ~C 5 (the hydrocarbon portion) The polymer (F) according to claim 1, which is a compound represented by the formula:

4. The carboxyl group-containing vinyl monomer (CA) has the formula (II): 【Chemistry 3】 (In the formula: R is equal to or different from 1 , R 2 and R 3 is a hydrogen atom and C 1 ~C 3 R is independently selected from a hydrocarbon group; H C contains at least one carboxyl group and no hydroxyl group 2 ~C 10 (the hydrocarbon portion) The polymer (F) according to claim 1, which is a compound represented by the formula:

5. The carboxyl group-containing vinyl monomer (CA) has the formula (IIa): 【Chemistry 4】 (In the formula, R is equal to or different from 1 , R 2 and R 3 is a hydrogen atom and C 1 ~C 3 R' is independently selected from a hydrocarbon group; H C which contains a hydrogen atom or at least one carboxyl group and does not contain a hydroxyl group 1 ~C 5 (the hydrocarbon portion) The polymer (F) according to claim 1, which is a compound represented by the formula:

6. 2. Polymer (F) according to claim 1, wherein the molar ratio between repeating units (ii) and repeating units (iii) in polymer (F) is preferably comprised in the range of from 20:1 to 1:20, preferably from 10:1 to 1:10, more preferably from 1:5 to 5:1; even more preferably, said molar ratio is 1:

1.

7. 2. The polymer (F) according to claim 1, wherein the divalent group RO is selected from the group consisting of ether (-O-), ester (-O-CO-), ketone (-CO-), epoxide, and percarbonate (-O-CO-O-) groups.

8. (a) C such as tetrafluoroethylene (TFE), hexafluoropropylene (HFP), pentafluoropropylene and hexafluoroisobutylene 2 ~C 8 Fluoro- and / or perfluoroolefins; (b) C fluorides such as vinyl fluoride, 1,2-difluoroethylene, and trifluoroethylene 2 ~C 8 Hydrogen-containing monofluoroolefin; (c) Formula CH 2 =CH-R f0 (In the formula, R f0 is C 1 ~C 6 perfluoroalkyl ethylenes, each of which is a perfluoroalkyl group; (d) Chloro- and / or bromo- and / or iodo-C such as chlorotrifluoroethylene (CTFE) 2 ~C 6 Fluoroolefin 2. The polymer (F) according to claim 1, further comprising repeat units derived from one or more fluorinated comonomers (CF) different from VDF, preferably selected from the group consisting of:

9. A process for the preparation of a polymer (F), said process comprising polymerizing vinylidene fluoride (VDF) monomer, monomers (HA) and (CA) and, optionally, comonomer (CF) in an aqueous medium in the presence of a radical initiator, said process comprising: - continuously feeding an aqueous solution comprising monomer (HA) and monomer (CA); maintaining the pressure in said reactor above the critical pressure of vinylidene fluoride; A process including.

10. 10. The process of claim 9, wherein the radical initiator is an organic peroxide, preferably selected from the group consisting of dialkyl peroxides, diacyl peroxides, peroxyesters, and peroxydicarbonates.

11. 10. The process of claim 9, wherein a chain transfer agent is added to the polymerization.

12. An electrode-forming composition [composition (C)], a) at least one electrode active material (AM); b) at least one binder (B), wherein the binder (B) comprises at least one polymer (F) according to any one of claims 1 to 8; c) at least one solvent (S); d) optionally, at least one conductive agent; An electrode-forming composition [composition (C)] comprising:

13. Use of the electrode-forming composition (C) according to claim 12 in a process for the manufacture of an electrode [electrode (E)], the process comprising: (A) providing a metal substrate having at least one surface; (B) providing an electrode-forming composition [composition (C)] according to claim 12; (C) applying the composition (C) provided in step (B) onto at least one surface of the metal substrate provided in step (A), thereby providing an assembly comprising a metal substrate coated on at least one surface with the composition (C); (D) drying the assembly provided in step (C); (E) subjecting the dried assembly obtained in step (D) to a compression step to obtain the electrode (E) of the present invention. Including, use.

14. An electrode [Electrode (E)] obtained by the process according to claim 13.

15. Electrochemical device comprising at least one electrode (E) according to claim 14.